Integrating climate-smart agriculture in regional policy through a fast-track process: Experience from Central America and the Dominican Republic - Le Coq, Jean-François; Martínez Barón, Deissy; Veeger, Marieke; Meza, Laura; Loboguerrero Rodriguez, Ana María (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Transforming agriculture to respond to the challenges of climate change requires the appropriate integration of solutions into public policy. While the role of science in mainstreaming climate change is recognized at the international and national level, especially for raising awareness and agenda-setting, the role of science for policy construction has been less analyzed. We analyze the successful case of the prompt formulation and adoption of the regional strategy for climate-smart agriculture for the SICA region (Central America and Dominican Republic), as a way to address both adaptation and mitigation issues while promoting food security and agricultural development. Mobilizing an analytical framework derived from policy process and science-policy interaction literature, we identify key factors that enabled this process. These factors encompass a combination of institutional and political long- and short-term characteristics of the regional policy arena, science-policy interactions, engagement relationships as well as methodological features. Our findings contribute to the discussion on science-policy engagement strategy to encourage agricultural transformation in a climate change context.